Initial Reports of the Deep Sea Drilling Project 1986
DOI: 10.2973/dsdp.proc.87.123.1986
|View full text |Cite
|
Sign up to set email alerts
|

Air Gun-Ocean Bottom Seismograph Seismic Structure across the Japan Trench Area

Abstract: A number of controlled-source seismic refraction studies using an ocean bottom seismograph (OBS) array have been made in the Japan Trench area recently. This report focuses on results from airgun data of two experiments. The first carried out in 1981, had a 250 km-long profile along the 3000-m depth contour on the landward side of the trench. The second experiment, conducted in 1982, had a 300-km-long profile along the inner lower trench slope and also included two profiles perpendicular to the trench axis. Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In the landward area of the 2 km isobath, however, clear westward dipping plate boundary was shown by the hypocenter distribution (Hasegawa et al, 1987;. As a static character, for example, the seismic wavespeed structures between the two regions are almost the same except for the thickness of low wavespeed materials in the part shallower than 10 km (Suyehiro et al, 1990), whereas the seismic activities which may indicate the dynamical characteristics are different between the two regions. This seems to reflect the spatial difference in the physical condition of the interplate coupling between the oceanic and the landward plate (Kawakatsu and Seno, 1983;Urabe, 1987).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the landward area of the 2 km isobath, however, clear westward dipping plate boundary was shown by the hypocenter distribution (Hasegawa et al, 1987;. As a static character, for example, the seismic wavespeed structures between the two regions are almost the same except for the thickness of low wavespeed materials in the part shallower than 10 km (Suyehiro et al, 1990), whereas the seismic activities which may indicate the dynamical characteristics are different between the two regions. This seems to reflect the spatial difference in the physical condition of the interplate coupling between the oceanic and the landward plate (Kawakatsu and Seno, 1983;Urabe, 1987).…”
Section: Discussionmentioning
confidence: 97%
“…A number of reflection and refraction experiments were carried out in the inner trench slope region off Sanriku, which reveal significant lateral heterogeneities in the crust and upper mantle structures related to the Pacific plate subduction (ex., Murauchi and Ludwig, 1980;Tamano et al, 1981). The wavespeed-depth model used for the present hypocenter determination is obtained by simplifying the models • proposed by Kanazawa et al (1985) and Suyehiro et al (1986) from the results of the refraction experiments using explosions and an airgun as artificial seismic sources. The P wavespeed structure used in the hypocenter calculation for the OBS data is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…No attenuation factor was considered except geometrical spreading. Incorporating relative amplitude information and constraining shallow structure using MCS results resolves wave speed gradients and depths of wave speed discontinuities better than previous models [Asano et al, 1981;Suyehiro et al, 1985Suyehiro et al, , 1986.…”
Section: Previous Obs/mcs Models and New Modelsmentioning
confidence: 99%
“…A comparison of the crustal structure at the Kurile Trench region with that of the Japan Trench area is very interesting, since the seismic wavespeed structure and deep seismic zone are continuous beyond the Kurile and Japan Trench junction Hasegawa et al 1983) and the Japan Trench region off Sanriku is one of the well investigated areas. A cross-section compiling the former results (Suyehiro et al 1986) is shown in Fig. 20.…”
Section: O M P a K I S O N O F T H E C R U S T A L S T R U C T U R mentioning
confidence: 99%
“…Topographical features of the subduction zone, such as trenches, island arcs and marginal seas, are shown. of seismic refraction and reflection experiments were carried out and outlined the transition from oceanic t o the continental structure (Ludwig et al 1966;Murauchi & Ludwig 1980;Nagumo, Kasahara & Koresawa 1980;Nasu et al 1980;Matsuzawa et al 1980;Tamano, Toba & Aoki 1981 ;Suyehiro et al 1985;Suyehiro, Kanazawa & Shimamura 1986). General features of the Japan Trench show a continental type upper crust as near as 40 km landward of the trench, a thick sedimentary low wavespeed prism beneath the lower inner trench slope and normal oceanic type crust seaward of the trench.…”
Section: Introductionmentioning
confidence: 99%